2021
DOI: 10.1108/jaoc-04-2021-0048
|View full text |Cite
|
Sign up to set email alerts
|

From interactive control to IT project performance: examining the mediating role of stakeholder analysis effectiveness

Abstract: Purpose This paper aims to unpack the relationship between the interactive use of project control systems (PCS) and project performance by examining the role of stakeholder analysis effectiveness in enacting this relationship. A conceptual framework was developed based on the stakeholder theory and the levers of control framework. Design/methodology/approach Partial least square-structural equation modelling analysis was conducted on the cross-sectional questionnaire data collected from 109 information techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 105 publications
(230 reference statements)
1
3
0
Order By: Relevance
“…First, prior studies have reported a positive relationship between the interactive use of project MCS and performance (e.g. Lu et al, 2011;Mir and Rezania, 2022;Rezania et al, 2016). Our results reaffirmed this relationship in the context of IT projects.…”
Section: Discussion Theoretical and Managerial Implicationssupporting
confidence: 88%
See 2 more Smart Citations
“…First, prior studies have reported a positive relationship between the interactive use of project MCS and performance (e.g. Lu et al, 2011;Mir and Rezania, 2022;Rezania et al, 2016). Our results reaffirmed this relationship in the context of IT projects.…”
Section: Discussion Theoretical and Managerial Implicationssupporting
confidence: 88%
“…Lu et al (2011) explored the moderating effect of interactive use of project MCS on the impact of knowledge management on marketing project performance. In the context of IT projects, a conditional positive relationship between the interactive use of project MCS and IT project performance has been observed (Mir and Rezania, 2022;Sakka et al, 2013), mediated by the stakeholder analysis effectiveness. In line with these findings, we hypothesize that:…”
Section: Interactive Use Of Mcs and Project Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The regression model showed that stakeholders' analysis and engagement had a positive significant influence on the level of project completion and project performance. Mir and Rezania (2022) study focused from interactive control to IT project performance: examining the mediating role of stakeholder analysis effectiveness. Partial least square-structural equation modelling analysis was conducted on the cross-sectional questionnaire data collected from 109 information technology (IT) projects.…”
Section: Systems Theorymentioning
confidence: 99%